The Impact of Trading Volume, Dividend Payout Ratio, Interest Rate, Inflation Rate on Stock Price Volatility of Banking Companies Listed in Indonesia Stock Exchange (IDX) 2011 â€“ 2015 - Humaira, Aida B1024131018 (Jurnal Manajemen Update, 2017)
ABSTRACTÂ Volatility is statistic measurement of stock price fluctuation during certain period of time (Firmansyah, 2006). In general, volatility in financial markets reflect the level of risk faced by investors because it describes the fluctuations movement of stock prices and uncertainty owned by the investor. The movement of stock price volatility depends on the information about stock prices that comes from inside and from outside the company. The purpose of this study is to determine the effect of trading volume, dividend payout ratio, interest ratio, and inflation rate towards stock price volatility.This study used secondary data with purposive sampling as the sampling technique. The population in this study is all banking companies listed in Indonesia Stock Exchange (IDX) from 2011 to 2015 with total sample of 16 companies. This study were analyzed by using multiple linier regression with ordinary least square method (OLS) and hypothesis test was conducted by using t-test, F-test at and adjusted R2.The result of analysis in this study show that trading volume does not significantly affect the stock price volatility while dividend payout ratio and inflation rate shows positive significant relationship towards stock price volatility and interest rate shows negative significant relationship with the independent variable. The simultaneous F-Test shows that all the independent variables significantly affect the dependent variable.Â